Midtrimester cervical elastography in pregnant women with a history of loop electrosurgical excision procedure (LEEP) - Hyun-Hwa Cha; Won Joon Seong; Hyun Mi Kim; Hyun-Joo Seol; Ji-Hee Sung; Hyun Soo Park; Han-Sung Hwang; Hayan Kwon; Yun Ji Jung; Ja-Young Kwon; Soo-young Oh (Scientific Reports, 2022)
Abstract We aimed to compare cervical elastographic parameters based on a previous loop electrosurgical excision procedure (LEEP) and to determine whether they can predict preterm delivery in pregnant women with a history of LEEP. This multicenter prospective case–control study included 71 singleton pregnant women at 14–24 weeks of gestation with a history of LEEP and 1:2 gestational age-matched controls. We performed cervical elastography using E-cervix and compared maternal characteristics, delivery outcomes, cervical length (CL), and elastographic parameters between the two groups. The median mid-trimester CL was significantly shorter in the LEEP group. Most elastographic parameters, including internal os (IOS), external os (EOS), elasticity contrast index (ECI), and hardness ratio (HR), were significantly different in the two groups. In the LEEP group, the sPTD group compared to the term delivery (TD) group showed a higher rate of previous sPTD (50% vs. 1.7%, p < 0.001), higher IOS and ECI (IOS: 0.28 [0.12–0.37] vs. 0.19 [0.10–0.37], p = 0.029; ECI: 3.89 [1.79–4.86] vs. 2.73 [1.48–5.43], p = 0.019), and lower HR (59.97 [43.88–92.43] vs. 79.06 [36.87–95.40], p = 0.028), but there was no significant difference in CL (2.92 [2.16–3.76] vs. 3.13 [1.50–3.16], p = 0.247). In conclusion, we demonstrated that a history of LEEP was associated with a change in cervical strain measured in mid-trimester as well as with CL shortening. We also showed that cervical elastography can be useful in predicting sPTD in pregnant women with previous LEEP.